Nonperturbative effective-field theory for two-leg antiferromagnetic spin ladders - Cabra, Daniel Carlos (2001)
We study the long wavelength limit of a spin-½ Heisenberg antiferromagnetic two-leg ladder, treating the interchain coupling in a nonperturbative way. We perform a mean ﬁeld analysis and then include the ﬂuctuations in an exact way. This allows for a discussion of the phase diagram of the system and provides an effective-ﬁeld theory for the low-energy excitations. The coset fermionic Lagrangian obtained corresponds toa perturbed SU(4)1 / U(1) conformal ﬁeld theory (CFT). This effective theory is naturally embedded in a SU(2)2 x Z2 CFT, where perturbations are easily identiﬁed in terms of conformal operators in the two sectors. Crossed and zigzag ladders are also discussed using the same approach.